Legal Framework and Regulatory Challenges in the Development of E-Commerce in Indonesia: Policy Analysis and Juridical Implications - Sembiring, Tamaulina Br.; Yolanda, Riska; Sitepu, Sofia Naliza; Siregar, Saskia Nabila; Putra, Raka Andika (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Technology advancements in transportation, communication, and information have quickened the pace of globalization. Online shopping (e-commerce) and other tech-and telecommunications-based activities have contributed to the expansion of businesses. Problems in applying corporate law to online transactions stem from questions about the function of law and the nature of legal progress. Law 11 of 2008, revised by Law 19 of 2016, pertaining to Electronic Information and Transactions; Law 7 of 2014, pertaining to Trade; and Government Regulation Number 82 of 2012, pertaining to the Implementation of Electronic Systems and Transactions, govern e-commerce regulations in Indonesia. However, there are still obstacles to its full application, such as problems with trust and accountability in proving electronic contracts and a lack of a complete knowledge of electronic transaction objects. The rule of law is an instrument for social renewal, social adaptation, and order maintenance. The complexity of social concerns has grown due to fast growth and modernization. Consequently, the creation of e-commerce-specific company laws seeks to promote long-term economic expansion by the establishment of norms that provide protection, clarity, and enforcement of the law.